Mutual Coupling Compensation in Non-Uniform Antenna Arrays using Inter-Element Spacing Restrictions - Tokan, F.; Gunes, F. (APPLIED COMPUTATIONAL ELECTROMAGNETICS SOC, 2011)
In the antenna array synthesis problems, most of the works in literature utilize isotropic elements. Thus, the mutual coupling effects between the array elements are neglected. It is obvious that an array antenna synthesized by neglecting the coupling effects cannot be used in the real world applications due to the possible incompatibilities between the desired and realized radiation patterns. In this work, two array antenna synthesis papers from literature are investigated in terms of mutual coupling effects so the necessary constraints are determined for the array geometry in order to compensate the coupling effects. Here, the same objectives of these two papers are achieved using the generalized pattern search (GPS) algorithm by considering the determined constraints for the inter-element spacings between the array elements. The resulted radiation patterns are validated with the computer simulation technology (CST) software with the aim of detecting possible incompatibilities due to the mutual coupling effects between the array elements. The simulation results verify that by using the constraints determined in this work, the radiation patterns obtained by pattern multiplication can provide the desired radiation demands also in the practical applications.
Keywords: GPS algorithm; mutual coupling effects; non-uniform array; null control; sidelobe suppression; PARTICLE SWARM OPTIMIZATION; PATTERN SEARCH ALGORITHMS; CONSTRAINED MINIMIZATION; GENETIC ALGORITHMS; SIDELOBE LEVEL; Engineering; Telecommunications